Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1371/journal.pone.0106420
|View full text |Cite
|
Sign up to set email alerts
|

No Impairment in Host Defense against Streptococcus pneumoniae in Obese CPEfat/fat Mice

Abstract: In the US and globally, dramatic increases in the prevalence of adult and childhood obesity have been reported during the last 30 years. In addition to cardiovascular disease, type II diabetes, and liver disease, obesity has recently been recognized as an important risk factor for influenza pneumonia. During the influenza pandemic of 2009, obese individuals experienced a greater severity of illness from the H1N1 virus. In addition, obese mice have also been shown to exhibit increased lethality and aberrant pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…We and others have observed that obese mice appear to exhibit significant alterations in leukocyte migration to the lungs after infection, particularly neutrophils .These abnormalities may be attributed to obesity‐induced impairments in pulmonary vascular homeostasis and enhanced susceptibility to acute injury . Neutrophils are known to ingest and kill bacteria, and elevated levels of PMNs may facilitate enhancements in host defenses against bacterial infections, contributing to host recovery.…”
Section: Discussionmentioning
confidence: 93%
“…We and others have observed that obese mice appear to exhibit significant alterations in leukocyte migration to the lungs after infection, particularly neutrophils .These abnormalities may be attributed to obesity‐induced impairments in pulmonary vascular homeostasis and enhanced susceptibility to acute injury . Neutrophils are known to ingest and kill bacteria, and elevated levels of PMNs may facilitate enhancements in host defenses against bacterial infections, contributing to host recovery.…”
Section: Discussionmentioning
confidence: 93%
“…Mancuso and colleagues (11,18) showed that obese, leptindeficient (ob/ob) mice exhibit increased susceptibility to infections with both gram-negative (K. pneumoniae) and gram-positive (Streptococcus pneumoniae) organisms, at 24 and 48 hours after inoculation, respectively, and that restoration of leptin levels could reverse the observed defects in bacterial clearance and survival (18). However, pulmonary host defense in hyperphagic CPE fat/fat mice (which manifest more modest metabolic abnormalities [25]) appeared to be normal at both 24 and 48 hours after infection with S. pneumoniae (19). Here, we report evidence of impaired pulmonary host defense in response to K. pneumoniae in both ob/ob and CPE fat/fat , as well as db/db and DIO, models of obesity, but with temporal variation.…”
Section: Discussionmentioning
confidence: 98%
“…Several animal models of obesity have been used to investigate the effects of obesity and associated comorbidities on the pulmonary immune response related to both acute and chronic lung diseases, including bacterial (11,12,18,19,27,29) and viral (9,28,39,40) respiratory infections, airway hyperresponsiveness (8,(41)(42)(43)(44)(45)(46), ARDS (5,7,12,30), pulmonary fibrosis (26), and chronic obstructive pulmonary disease (31). The most commonly employed mouse models of obesity include DIO, the hyperphagic mutant db/db, CPE fat/fat , and ob/ob strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High circulating leptin content in mice, elevated by diverse strategies, can compromise innate immunity in the lungs (502). A specific role for leptin is further supported by the observation of no adverse effects on lung defense in a leptin-independent mouse model of obesity (307). The precise role of leptin is complicated by indirect metabolic consequences of its manipulation and the widespread physiological impacts of obesity (479).…”
Section: Fatmentioning
confidence: 99%